Understanding the Degradation of Methylenediammonium and Its Role in Phase-Stabilizing Formamidinium Lead Triiodide - Duijnstee, Elisabeth A.; Gallant, Benjamin M.; Holzhey, Philippe; Kubicki, Dominik J.; Collavini, Silvia; Sturdza, Bernd K.; Sansom, Harry C.; Smith, Joel; Gutmann, Matthias J.; Saha, Santanu; Gedda, Murali; Nugraha, Mohamad I.; et al. (Journal of the American Chemical Society, 2023)
Formamidinium lead triiodide (FAPbI3) is the leading candidate for single-junction metal–halide perovskite photovoltaics, despite the metastability of this phase. To enhance its ambient-phase stability and produce world-record photovoltaic efficiencies, methylenediammonium dichloride (MDACl2) has been used as an additive in FAPbI3. MDA2+ has been reported as incorporated into the perovskite lattice alongside Cl–. However, the precise function and role of MDA2+ remain uncertain. Here, we grow FAPbI3 single crystals from a solution containing MDACl2 (FAPbI3-M). We demonstrate that FAPbI3-M crystals are stable against transformation to the photoinactive δ-phase for more than one year under ambient conditions. Critically, we reveal that MDA2+ is not the direct cause of the enhanced material stability. Instead, MDA2+ degrades rapidly to produce ammonium and methaniminium, which subsequently oligomerizes to yield hexamethylenetetramine (HMTA). FAPbI3 crystals grown from a solution containing HMTA (FAPbI3-H) replicate the enhanced α-phase stability of FAPbI3-M. However, we further determine that HMTA is unstable in the perovskite precursor solution, where reaction with FA+ is possible, leading instead to the formation of tetrahydrotriazinium (THTZ-H+). By a combination of liquid- and solid-state NMR techniques, we show that THTZ-H+ is selectively incorporated into the bulk of both FAPbI3-M and FAPbI3-H at ∼0.5 mol % and infer that this addition is responsible for the improved α-phase stability.